Configuration of the Volatile Aromatic Profile of Carob Powder Milled From Pods of Genetic Variants Harvested at Progressive Stages of Ripening From High and Low Altitudes - Antoniou, Chrystalla; Kyratzis, Angelos C.; Soteriou, Georgios A.; Rouphael, Youssef; Kyriacou, Marios C. (Frontiers in Nutrition, 2021)
Carob powder milled from coarse pulp kibbles bears the intense sweet aroma associated with carobs. It is increasingly valued as a substitute for cocoa and as a flavor-enhancing component of processed foods. However, Llittle is known about the effects impact of preharvest factors such as fruit maturity, genotype and altitude on the its volatile organic compounds (VOCs) composition of carob powder. The current study examined the VOCs composition of powder milled from pods of two genotypes cultivated at 15 m and 510 m altitude and harvested at six progressive stages of maturity, ranging from fully developed immature green (RS1) to late ripe (RS6). Fifty-six VOCs categorized into acids, esters, aldehydes, ketones, alcohols, furans and alkanes were identified through HS-SPME GC-MS analysis. Maturity was the most influential factor, followed by altitude and least by genotype. Aldehydes and alcohols correlated positively (r=0.789; p<0.001), both accumulated in immature carobs and decreased with progressive ripening, leading toresulting in the attenuation of green grassy aroma. Conversely, Aacids increased with ripening and dominated the carob volatilome at full maturity, correlating negatively with aldehydes and alcohols (r=-0.835 and r=-0.950, respectively; p<0.001). The most abundant VOC throughout ripening (17.3 – 57.7%) was isobutyric acid, responsible for the characteristic cheesy-acidic-buttery aroma of carob powder. The pleasurable aroma detected at the immature stages (RS2-RS3) was traced to isobutyrate and methyl isobutyrate esters, rendering unripe green carob powder a potential admixture component for improving the aroma of novel food products that warrants further investigation. The higher abundance of acids obtained at lLower altitude related mainly tofavored the accumulation of acids linked to less pleasant aroma, whereas the dominant isobutyric acid was more abundant at higher altitude. This constitutes a significant indication that higher altitude enhances the characteristic carob-like aroma and sensory qualities quality of carob powder.